2017
DOI: 10.1021/acscatal.7b03081
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Intermolecular Allylic Functionalization of Unactivated Internal Alkenes

Abstract: The asymmetric allylic functionalization of unactivated internal alkenes is an emerging strategy for the conversion of simple unsaturated starting materials into a diverse range of enantioenriched products. This Perspective summarizes the development of reactions wherein a chiral catalyst facilitates the intermolecular stereoselective reaction between an achiral unactivated internal alkene and a reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 96 publications
(172 reference statements)
0
18
0
Order By: Relevance
“…Oxidative allylic C­(sp 3 )–H bond functionalization of simple alkenes with carboxylic acids, i.e., allylic C­(sp 3 )–H acyloxylation, is a powerful tool for preparing synthetically useful allyl esters. Various methodologies have been developed to date to oxidize the allylic C­(sp 3 )–H bond using peracids and high-valent metal complexes as stoichiometric oxidants; however, owing to the high reactivity of those oxidants, the functional group tolerance is narrow, and stoichiometric amounts of metal wastes are produced as byproducts. Aiming to overcome the narrow substrate scope and environmental unfriendliness for allylic C­(sp 3 )–H acyloxylation, Heumann and Åkermark et al developed palladium-catalyzed allylic C­(sp 3 )–H acyloxylation of cyclic alkenes in the presence of a catalytic amount of 1,4-benzoquinone (1,4-BQ) together with more than stoichiometric amounts of MnO 2 or a catalytic amount of Cu­(OAc) 2 with O 2 as the oxidants in acetic acid, giving allyl acetates in good yield without overoxidized products (Scheme (a)). , Uemura et al demonstrated that a combination of tert -butyl hydroperoxide and TeO 2 was effective for acyloxylation of the allylic C­(sp 3 )–H bond of cyclic alkenes catalyzed by PdCl 2 /AgOAc (Scheme (b)), although terminal alkenes were not applied in this palladium-catalyzed allylic oxidation due to the facile isomerization of the alkene moiety.…”
mentioning
confidence: 99%
“…Oxidative allylic C­(sp 3 )–H bond functionalization of simple alkenes with carboxylic acids, i.e., allylic C­(sp 3 )–H acyloxylation, is a powerful tool for preparing synthetically useful allyl esters. Various methodologies have been developed to date to oxidize the allylic C­(sp 3 )–H bond using peracids and high-valent metal complexes as stoichiometric oxidants; however, owing to the high reactivity of those oxidants, the functional group tolerance is narrow, and stoichiometric amounts of metal wastes are produced as byproducts. Aiming to overcome the narrow substrate scope and environmental unfriendliness for allylic C­(sp 3 )–H acyloxylation, Heumann and Åkermark et al developed palladium-catalyzed allylic C­(sp 3 )–H acyloxylation of cyclic alkenes in the presence of a catalytic amount of 1,4-benzoquinone (1,4-BQ) together with more than stoichiometric amounts of MnO 2 or a catalytic amount of Cu­(OAc) 2 with O 2 as the oxidants in acetic acid, giving allyl acetates in good yield without overoxidized products (Scheme (a)). , Uemura et al demonstrated that a combination of tert -butyl hydroperoxide and TeO 2 was effective for acyloxylation of the allylic C­(sp 3 )–H bond of cyclic alkenes catalyzed by PdCl 2 /AgOAc (Scheme (b)), although terminal alkenes were not applied in this palladium-catalyzed allylic oxidation due to the facile isomerization of the alkene moiety.…”
mentioning
confidence: 99%
“…Although the Tambar group suggested a hydrogen-bonding process for the enophile 2 activation in the SbCl 5 -4-catalyzed heteroene reaction, 12,13 we hypothesized an added protonation process of 2 to generate a zwitterionic complex ( of substrate alkenes in the following allylic oxidation step. The other one is that enophile 2 is protonated at its internal N atom [HNSO] + instead, and the terminal O atom is reserved as an acceptor for the allylic hydrogen of alkenes.…”
Section: Introductionmentioning
confidence: 91%
“…Homoallylic nitroalkanes, an important subclass of alkenes, are versatile building blocks in organic synthesis and provide precursors to amines relevant to biologically active N-containing compounds . Metal-catalyzed allylic alkylation reactions have become popular toward the preparation of functionalized olefins under mild reaction conditions . In this respect, Tsuji–Trost-type allylation of nitroalkanes has received much attention because the resultant homoallylic products are precursors to their homoallylic amine congeners …”
Section: Introductionmentioning
confidence: 99%